Biased Random Key Genetic Algorithm Dengan Insertion Dan Gender Selection Untuk Capacitated Vehicle Routing Problem With Time Windows - Rochman, Auliya Noor; , Dr. Hari Prasetyo (2016)
Vehicle Routing Problem (VRP) is often found in industrial practices particularly when the manufacturer has to ship their product to a number of customers/outlets. In reality, the distribution process is typically restricted by the capacity of the truck and the working hours at the distributor. This type of VRP is also known as Capacitated Vehicle Routing Problem with Time Windows (CVRPTW). This CVRPTW is a Non Polynomial hard problem, thus designing an efficient and effective algorithm to find the optimal solution is one of the main challenging task. In this research, a Biased Random Key Genetic Algorithm (BRKGA) designed and coded in MATLAB to solve the CVRPTW for the case of distributing soft drink. The standard BRKGA is then modified by applying chromosome insertion into the initial population and defining chromosome gender for parent undergoing crossover operation. The performance of the established algorithms are then compared to a heuristic procedure for solving a soft drink distribution. In this research, some findings are revealed (1) in terms of the total distribution cost BRKGA with insertion returns a cost saving of 39% compared to that of from the heuristics, (2) BRKGA with selection gender selection could further improve the performance of the standard BRKGA, but BRKGA with gender selection tends to yield worse results compared to that of obtained from the standard BRKGA.